2021
DOI: 10.21203/rs.3.rs-842089/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of the effect of Kahoot! on academic achievements and student performance

Abstract: Kahoot!-based serious games have received international attention and obtained more than two billion players across over 200 countries and areas (Kahoot!, 2021). However, scanty studies have systematically examined their effect on educational outcomes using a meta-analysis. Through a meta-analysis using Stata/MP 14.0, this study concludes that Kahoot!-based serious games could significantly improve academic achievements and student performance, that the educational level of participants could not predict Kahoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…This aligns withYunus et al's (2019) assertion that gamification and direct experiences contribute to learning development and skills mastery, aiding in the accurate recall of facts. The study supportsYu's (2021) work, where Kahoot! positively influenced learning development, leading to improved literary and English language capacity.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This aligns withYunus et al's (2019) assertion that gamification and direct experiences contribute to learning development and skills mastery, aiding in the accurate recall of facts. The study supportsYu's (2021) work, where Kahoot! positively influenced learning development, leading to improved literary and English language capacity.…”
supporting
confidence: 89%
“…in fostering deeper comprehension, surpassing traditional lecture methods. Supporting evidence from Chiang (2020), Wang et al (2020), Zarzycka-Piskorz (2019), Mohammed (2021), Kurniawan et al (2019), Yunus et al (2019), Yu (2021), andPutri et al (2021) further validates the positive impact of the Kahoot! game-based approach.…”
Section: Difference In Literary Comprehension Achievementmentioning
confidence: 79%
“…Despite the popularity of ML based on RCIC, there is no consensus on whether it contributes to improving academic performance or not. According to a recent meta-analysis in the pre-publication phase based on RCIC interventions with Kahoot ( Yu, 2021 ), has been shown to significantly improve the academic performance of students. The present meta-analysis examined whether the effect of RCIC with different tools, beyond that Kahoot, improved the academic performance in the students.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present study's findings, researchers frequently described Kahoot! as an enjoyable, entertaining, and even amusing tool [3,9,30]. Furthermore, according to a study conducted by Pratama, et al [8] it was found that individuals who participated in Kahoot!…”
Section: Facilitatingmentioning
confidence: 99%